Equivalence in Translation - Ghanooni, Ali Reza (Armenian Folia Anglistika, 2011)
The author of the article refers to the theory of equivalence of the original and the target texts. The author mentions that though the problem of equivalence in translation was widely discussed in the second half of the previous century, it has caused much controversy. Discussing the existing controversial viewpoints the author of the article criticizes each of them and specifies his own viewpoint on the issue discussed.